Investigation of plasma‐induced chemistry in organic solutions for enhanced electrospun PLA nanofibers. Issue 6 (24th March 2018) - Rezaei, Fatemeh; Gorbanev, Yury; Chys, Michael; Nikiforov, Anton; Van Hulle, Stijn W. H.; Cos, Paul; Bogaerts, Annemie; De Geyter, Nathalie
Abstract : Electrospinning is a versatile technique for the fabrication of polymer‐based nano/microfibers. Both physical and chemical characteristics of pre‐electrospinning polymer solutions affect the morphology and chemistry of electrospun nanofibers. An atmospheric‐pressure plasma jet has previously been shown to induce physical modifications in polylactic acid (PLA) solutions. This work aims at investigating the plasma‐induced chemistry in organic solutions of PLA, and their effects on the resultant PLA nanofibers. Therefore, very broad range of gas, liquid, and solid (nanofiber) analyzing techniques has been applied. Plasma alters the acidity of the solutions. SEM studies illustrated that complete fiber morphology enhancement only occurred when both PLA and solvent molecules were exposed to pre‐electrospinning plasma treatment. Additionally, the surface chemistry of the PLA nanofibers was mostly preserved. Abstract : Solutions of polylactic acid in chloroform and 5, 5‐ N ‐dimethylformamide are subject to pre‐electrospinning plasma treatment (PEPT). EEM, EPR, OES, NMR, XPS, and other analyses are performed. The enhanced conductivity of the solutions is ascribed to the formation of HCl during PEPT. The synergistic effect of chemical changes leads to nanofibers with enhanced uniformity.